Resilience of Social-ecological Systems to Human Perturbation: Assessing Dongting Lake in China - Xu, Li; Marinova, Dora; Guo, Xiumei (Canadian Center of Science and Education, 2015)
This paper conducts an assessment on the social-ecological resilience of China’s Dongting Lake (and its three sections – East, West and South Dongting Lake) in relation to the perturbations of the Three Gorges Dam using a set of resilience-based indicators. Expert scoring is applied to identify the different states of the lake and their resilience levels. Based on equal weighting for all indicators and using the technique of ordering preferences according to similarity to the ideal solution, an assessment of the social-ecological resilience of Dongting Lake is generated. The results show that East Dongting has higher ability to absorb perturbations than South and West Dongting which have relatively low resilience to the changes triggered by the impoundment of the Dam. Effective adaptation measures are needed for the lake to be able to better absorb these perturbations and be sustainable in the long run.